Control, access and professionalism: a qualitative evaluation of Australian dental practitioners attitudes to expanding medicare to include more dental services - Alexander C. L. Holden; Matt S. Hopcraft (BMC Oral Health)
Abstract Background Australia benefits from one of the most comprehensive publicly-funded health systems in the world, however, dentistry hardly features at all within the provisions of the scheme. As a result, the majority of dental care in Australia is provided within the private sector, with the States and Territories providing a small eligibility-controlled service. This research examines Australian dental practitioner’s attitudes to the conceptual expansion of Medicare to include more dental services. Methods This research utilises the qualitative methodology of thematic analysis to explore the attitudes and beliefs of dental practitioners in relation to expanding Medicare to include more dental services. Participants were recruited from a pool of dental practitioners who had responded to a survey on Medicare expansion to include dental care. Participants were interviewed using an interview guide, with semi-structured questions. Interviews took place online and were recorded. Iterative rounds of coding allowed constituent themes to emerge for analysis. Results A total of 12 participants were interviewed before saturation was reached, with three main overarching themes developing through successive rounds of coding. The three themes identified were: Professional Factors; Nature and Organisation of a Potential Scheme; and, Oral Health as Health. Conclusions Professional attitudes to the expansion of Medicare are not simple or binary considerations. Dental practitioners are highly sensitive to the high cost of dentistry as an impediment to access and would welcome government assistance to help those who struggle with the costs of private dentistry to experience better oral health. However, participants also shared their anxieties in relation to how Medicare increasing its scope in relation to dentistry might herald unwelcome impacts for business models in dental care. Participants also noted the staunch self-interest to opposing comprehensive Medicare expansion from the Australian Dental Association.